Reciprocal Peer Coaching: A Critical Contributor to Implementing Individual Leadership Plans. (18th March 2013) - Goldman, Ellen; Wesner, Marilyn; Karnchanomai, Ornpawee
Abstract Billions of dollars are spent annually on programs to develop organizational leaders, yet the effectiveness of these programs is poorly understood. Scholars advise that value is enhanced by the development of individual leadership plans at program completion, followed by implementation experience with subsequent coaching and reflection. The literature discusses coaching on specific skills in individual plans; research is lacking regarding coaching's value for the individual plan implementation process as a whole. In addition, there is scant literature concerning the use of reciprocal peer coaching in leadership development. This article presents the findings of research aimed at understanding the experience of individuals who completed a leadership development program, prepared individual leadership plans at completion, and then engaged in a process that included reciprocal peer coaching to help them implement their plans. The major contributions of the study concern the importance of the support structure provided, the nature of the benefits identified from giving as well as receiving coaching, and the specification of a transformational learning process regarding both the implementation of individual leadership plans and engagement in reciprocal peer coaching. While the study was conducted in a medical educational setting, the findings have implications for leadership development programs in other areas of education, as well as other organizational settings.